Energy materials - Bruce, Duncan W.; O'Hare, Dermot.; Walton, Richard I. (Inorganic materials series., 2011)
"Following the success of Inorganic Materials, the concept of the original book will be updated and extended to reflect the recent expansion of research and applications in inorganic material chemistry, and its interfaces with physics, biology and materials science. Inorganic materials will be separated into five areas based on their physical properties: porous, functional oxides, molecular, low-dimensional and electronic materials. Each area will be presented in one volume and each chapter will cover recent research areas within the contributors' field of knowledge, providing a clear and useable introduction to that field. The chapters of the book will be self-contained and relate to a different area of the volume's general subject matter. This volume looks at inorganic materials with special electronic properties and is proposed as follows: polymer electrolytes, photonic crystals, low molar mass OLEDs, and polymer LEDs"--